1999
DOI: 10.1046/j.1365-2222.1999.00551.x
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐inflammatory effect of roxithromycin in patients with aspirin‐intolerant asthma

Abstract: Although roxithromycin does not have antileucotriene effects, it has an antibronchial inflammatory effect associated with eosinophilic infiltration. This study raises further interesting therapeutic possibilities and warrants further trials of new approaches to the treatment of aspirin-intolerant asthma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
1
2

Year Published

2001
2001
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(49 citation statements)
references
References 20 publications
0
46
1
2
Order By: Relevance
“…Roxithromycin, one of the macrolide antibiotics, has been reported to suppress sputum eosinophils and eosinophil cationic protein in asthmatic patients (38).…”
Section: Discussionmentioning
confidence: 99%
“…Roxithromycin, one of the macrolide antibiotics, has been reported to suppress sputum eosinophils and eosinophil cationic protein in asthmatic patients (38).…”
Section: Discussionmentioning
confidence: 99%
“…The protective effect of RXM was also evaluated on airway responsiveness to the sulpyrine provocation test. Shoji et al [172] addressed the question of whether this protective activity is associated with a reduction in aspirin-induced excretion of urinary leucotriene E4 (u-LTE4). The latter is important as a marker of cysteinyl leucotriene overproduction that participates in the pathogenesis of aspirinintolerant asthma.…”
Section: Macrolides and Asthmamentioning
confidence: 99%
“…[17][18][19][20][21][22][23][24][25][26] A 2005 Cochrane review concluded that there was insufficient evidence to confirm or refute the role of macrolide treatment in chronic asthma. 1 Since 2005, 3 additional trials of macrolides in chronic adult asthma have reported patient-oriented outcomes.…”
Section: Previous Studiesmentioning
confidence: 99%